SISTEM PAKAR: PENERAPAN METODE FORWARD CHAINING UNTUK IDENTIFIKASI TANAMAN HIAS BERDASARKAN CIRI STRUKTUR TAKSONOMI - DIATMIKA, KETUT TUTUR; Suardana, Putu; Winata, I Gede Arya; Octavia, I Gusti Ayu Adiani; Marta Dinata, Kadek Prima Giant; Permana, Agus Aan Jiwa (Universitas Pendidikan Ganesha, 2024)
An expert system is a subset of artificial intelligence that widely applies specialized knowledge to address human-level problems requiring specific expertise. Forward Chaining is one of the techniques used in the inference engine, which performs forward tracking based on known facts to draw conclusions. In this study, forward chaining is employed for the identification of ornamental plants based on their taxonomic structure characteristics by tracing facts present in the knowledge base. The dataset used to construct the knowledge base in this research is derived from literature sources such as journals and published scientific articles. This research utilizes the Prolog programming language to build the expert system with the goal of identifying ornamental plants based on their taxonomic structure. The expert system is designed to facilitate the identification process effectively and efficiently. With the forward chaining method and the use of Prolog, this expert system is capable of identifying ornamental plants based on the characteristics of their taxonomic structure.